Experiences Among School Personnel and School Nurses on Educational Adaptations for Students With CFS/ME: A Qualitative Interview Study - Similä, Wenche Ann; Rø, Torstein Baade; Nøst, Torunn Hatlen (Frontiers in Pediatrics, 2021)
Abstract Objectives To explore teachers, counselors, and school nurses’ experiences with adaptation of education for students with CFS/ME. Design A qualitative study with focus group and individual interviews performed face-to-face or digitally between November 2020 and March 2021. Data were analyzed using systematic text condensation. Participants Six teachers, two counselors and four school nurses in secondary and high school participated. Results To adapt education for students with CFS/ME was challenging, especially in the period before a diagnosis was set. The challenges were related to identifying the students’ adaptational needs, maintaining a teacher-student relationship due to school absence, and difficulties in maintaining continuity of education, and uncertainty regarding the diagnosis. Successful adaptations were related to quickly reacting to school absence, early referral to educational psychological services, a close collaboration with the school management, and development of digital teaching for students with CFS/ME. Interdisciplinary collaboration and a clear and constructive plan with adaptive measures including maintained teacher-student communication, and both educational and social adaptations may be useful to prevent the losses young people with CFS/ME experience. Conclusion Early interdisciplinary collaboration to adapt education and social life at school for students with CFS/ME, may support teachers, counselors, and school nurses in their efforts to adapt schooling and prevent losses related to academic and social development, in students with CFS/ME.